The Effect of Advertising, Product Quality, and Brand Image on Repurchase Interest for Samsung Smartphones in Surabaya - Maulidiyah, Akhmadah; Soebiantoro, Ugy (Management Science Research Journal, 2025)
The increasingly competitive smartphone industry in Indonesia has prompted companies to innovate in advertising, product quality, and brand image to boost consumer repurchase interest. This study was conducted to analyze the contribution of these three factors to the repurchase interest in Samsung smartphones in Surabaya. This study employed a quantitative approach using a purposive sampling technique with 114 respondents. Data were collected via an online questionnaire. The criteria for respondents included being at least 17 years old, having used a Samsung smartphone for at least one year, and being a resident of Surabaya. The data analysis was performed using the Partial Least Square (PLS) method to test for validity, reliability, and hypotheses. The research results indicate that advertising and brand image have a positive and significant effect on repurchase interest. In contrast, product quality was found to have a positive but not significant effect on repurchase interest.